PENGAJUAN PENINJAUAN KEMBALI OLEH JAKSA PENUNTUT UMUM BERDASARKAN PASAL 30C UU NO. 11 TAHUN 2021 TENTANG PERUBAHAN UU NO. 16 TAHUN 2004 TENTANG KEJAKSAAN DIKAITKAN DENGAN PUTUSAN MK NO. 33/PUU-XIV/2016 DALAM PERSPEKTIF KEPASTIAN HUKUM DAN KEADILAN - Arman Tjoneng; Dian Narwastuty (Faculty of Law, Maranatha Christian University, 2023)
With the ratification of the prosecutor's law in 2021, it finally caused a polemic regarding the authority of the public prosecutor in filing a judicial review. The counter-opinion argues that the framers of the law did not understand the norms in the existing legislation. On the other hand, MK Decision No.33/PUU-XIV / 2016 which states that the review by the Public Prosecutor contrary to the code of Criminal Procedure is final and binding for anyone. Therefore, the prosecutor's authority in applying for judicial review is considered unlawful. But on the other side, the Internal Affairs of the prosecutor's actually took another view and strongly supported the authority for filing a judicial review by the prosecutor's under the new law. Based on this study, which uses normative juridical methods and legislative approaches and conceptual approaches, then with the ratification of the prosecutor's law in 2021, it is considered to provide more legal certainty for the authority of the public prosecutor in filing a judicial review and providing space for “justice” for victims and as an effort to correct and improve in realizing justice.